Analisis Faktor Yang Berpengaruh Terhadap Kinerja Pegawai Rumah Sakit - Setyowati, Yayuk (Kajian Ekonomi dan Bisnis, 2018)
This study aims to analyze : (1) the effects of work culture towards employees’ performance in PKU Muhammadiyah Gamping hospital (2)the effects job satisfaction towards employees’ performance in PKU Muhammadiyah Gamping hospital (3) the effects of work culture and job satisfaction towards employees’ performance in PKU Muhammadiyah Gamping hospital. This study was casual associative study by using quantitative approach. The sample in this study is the entire population of PKU Muhammadiyah Gamping hospital employees, amounting to 50 people.Data were collected using a questionnaire which was tested for the validity (CFA)and reliability (Cronbach Alpha). The analysis technique used multiple regression analysis. The results of this study indicate that: (1) work culture has a positive influence but not significant on the performance of PKU Muhammadiyah Gamping hospital employees’ with a beta value of 0.085 and a significance value of 0.632. The contribution of work culture and job satisfaction to performance (R2) is 0.139 or 13.9%.